Clinical characteristics and severity markers in hospitalized COVID-19 patients from western Mexico: a comparative analysis of Delta and Omicron variants - Hazael Ramiro Ceja-Gálvez; Cristian Oswaldo Hernández-Ramírez; Alejandra Natali Vega-Magaña; Jorge Hernández-Bello; Kevin Javier Arellano-Arteaga; Francisco Javier Turrubiates-Hernández; Diana Lourdes Padilla-Borquez; José Francisco Muñoz-Valle (Frontiers Media S.A., 2024)
IntroductionCOVID-19 is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a virus notable for its rapid mutation rate, which has led to the emergence of various variants such as Delta and Omicron, each with potentially different levels of transmissibility and virulence. Therefore, this study aims to compare clinical charactheristics and markers associated with the severity of COVID-19 in hospitalized patients from western Mexico who were infected with the Delta and Omicron variants of SARS-CoV-2.MethodsThis cross-sectional study involved 66 patients hospitalized for COVID-19, diagnosed by RT-qPCR. SARS-CoV-2 variants were identified through whole genome sequencing using the COVIDseq platform from Illumina. Upon admission, patients underwent a clinical history assessment, blood gas analysis, and blood biometry. Additionally, several tests and markers were measured, including the percentage of neutralizing antibodies, erythrocyte sedimentation rate (ESR), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNFα), D-dimer, lactate dehydrogenase (LDH), C-reactive protein (CRP), and ferritin.Results and discussionPatients hospitalized with the Omicron were found to be older, compared to those infected with the Delta (64 vs. 54 years, p = 0.006). Additionally, a higher proportion of male patients were observed in the Omicron compared to the Delta (p = 0.029). Both Omicron and Delta variants were associated with lymphopenia, although the lymphocyte count was lower in Omicron (0.9 vs. 0.56 10x3/L; p = 0.007). The COVID-GRAM scale indicated a high risk for severe disease in both groups, but the score was higher in Omicron compared to Delta (157 vs. 128 points; p = 0.0004). Patients infected with Omicron exhibited a lower percentage of neutralizing antibodies than those with Delta (35.99 vs. 81%; p < 0.05), regardless of their vaccination status. Among the markers assessed, globular ESR was found to be lower in Omicron compared to Delta (30.5 vs. 41.5 mm/h; p = 0.001), while ferritin levels were higher in patients infected with the Omicron (1,359 vs. 960.6 μg/L; p = 0.007). In patients with severe COVID-19, markers such as lymphopenia, neutralizing antibody levels, ferritin, and COVID-GRAM scores are elevated in the Omicron variant, while only the leukocyte count and ESR for the Delta variant.